Unfulfilled Guarantees: Impacts of Law and Regulations Concerning Inter-Religious Relations on Religious Freedom in Indonesia - Yasin, Yasin; Mantu, Rahman (IAIN Samarinda, 2021)
The condition of interfaith relations in Indonesia faces many challenges as intolerance increasingly occurs in various regions. The action can be seen from various violations of freedom of religion and belief, the prohibition of establishing houses of worship, and violence against minorities. One of the causes of these problems relates to the law and several regulations in interfaith relations in Indonesia. This article tries to look at the regulations and legal aspects of interfaith relations and their impact on the conditions of diversity in Indonesia. Using an empirical-legal approach, this article explores legal materials and phenomena related to the interfaith relation in Indonesia. This article reveals that the Constitution has been firmly guaranteeing and protecting all citizens from expressing their beliefs. Nevertheless, several cases show a contrary of the law objectives on interfaith relations in Indonesia. Moreover, in some particular cases, the state seemed to be absent in the locus of incident and favor of freedom violation victims instead.